Norton scale for predicting prognosis in elderly patients undergoing trans-catheter aortic valve implantation: A historical prospective study. Issue 6 (June 2016) - Rabinovitz, Edith; Finkelstein, Ariel; Ben Assa, Eyal; Steinvil, Arie; Konigstein, Maayan; Shacham, Yacov; Yankelson, Lior; Banai, Shmuel; Justo, Dan; Leshem-Rubinow, Eran
Abstract: Background: The Norton scale is traditionally used to assess the risk of pressure ulcers. However, recent studies have shown its prognostic utilization in elderly patients with diverse medical conditions. The association between low admission Norton scale scores (ANSS), complications, and mortality in elderly patients following trans-catheter aortic valve implantation (TAVI) has never been studied. We aimed to determine if low ANSS (≤16) is associated with complications and 30-day and 1-year mortality in elderly patients undergoing TAVI. Methods: The medical charts of elderly (≥70 years) TAVI patients at the Tel-Aviv Medical Center, a tertiary medical center, were studied for the following measurements: ANSS, demographics, co-morbidities, complications during hospitalization, and 30-day and 1-year mortality. Complications included: an atrio-ventricular block, stroke, and vascular complications. Results: The cohort included 302 elderly patients: 179 (59.3%) were women; the mean age was 83.3 ± 5.1 years. Following TAVI, 112 (37.1%) patients had complications other than pressure ulcers, 10 (3.3%) patients died within 30 days, and 42 (13.9%) patients died within one year. Overall, 36 (11.9%) patients had low ANSS. 1-year mortality rates were almost three times higher in patients with low ANSS relative to patients with high ANSS (27.8% vs. 12.0%; the relative risk 1.1; p = 0.018). A stepwise logistic regression analysis showed that ANSS was independently inversely associated with 1-year mortality ( p = 0.018). Complications and 30-day mortality rates were similar in both groups. Conclusions: Low ANSS are associated with 1-year mortality after TAVI. The Norton scale may therefore be used as an additional tool for elderly patient selection before TAVI.